The Theory of Hyperlipidemic Memory of Type 1 Diabetes - Nwosu, Benjamin Udoka (Frontiers in Endocrinology, 2022)
Partial clinical remission (PR) of type 1 diabetes (T1D) is characterized by continued endogenous production of insulin and C-peptide following the diagnosis and the introduction of exogenous insulin therapy. PR is associated with improved glycemic control and reduced prevalence of diabetes complications. The theory of hyperglycemic memory was proposed to explain this concept of improved glycemic outcomes in remitters (those who experienced PR) versus non-remitters (those who did not experience PR). However, this theory is incomplete as it does not explain the dichotomy in early lipid phenotypes in T1D based on PR status, which is an understudied area in diabetology and lipidology. To fill this knowledge gap, we propose the Theory of Hyperlipidemic Memory of T1D. This theory is premised on our 5-year research on early post-diagnostic dichotomy in lipid phenotypes between remitters and non-remitters across the lifespan. It provides a more rigorous explanation for the differences in lifelong atherosclerotic cardiovascular disease (ASCVD) risk between remitters and non-remitters. We conducted 4 clinical studies in pediatric and adult subjects with diabetes mellitus to characterize the particulars of the hyperlipidemic memory. In the first investigation, we explored the impact of the presence or absence of PR on lipid parameters in children and adolescents with T1D. In the second, we investigated whether pubertal maturation influenced our findings in T1D; and whether these findings could be replicated in healthy, non-diabetic children and adolescents. In the third, we leveraged our findings from T1D and controls to investigate the mechanisms of early lipid changes in T2D by comparing the earliest lipid phenotype of subjects with type 2 diabetes (T2D) to those of remitters, non-remitters, and controls. In the fourth, we investigated the impact of PR on the earliest lipid phenotypes in adults with T1D and compared these early lipid data to those of T2D subjects and controls. This body of work across the lifespan in children, adolescents, and adults supports the Theory of Hyperlipidemic Memory. This new theory clarifies why PR largely determines the risks for early-phase dyslipidemia, mid-term microvascular disease risk, and long-term ASCVD risk in subjects with T1D.